Research Brief #13: Proceedings of the 2nd Annual Scientific Symposium August 13-14, 2013. - Shrestha, Raman.; Manohar, Swetha.; Klemm, Rolf. (Tufts University. Tisch Library., 2016)
This briefing details the proceedings of the 2nd Annual Scientific Symposium in Kathmandu, Nepal on August 13-14, 2013 under the theme "Science and Policy for Health, Agriculture and Economic Growth". It contains a list of all presenters and a summary of the each presenter's research. It also contains a list of the poster presenters and topics. Keywords: CRSP, Research Brief, priorities.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy